Control of a 3 level PWM inverter for grid-connected photovoltaic generation systems - Yu, Chengzhuo (Nanyang Technological University, 2023)
As an important source of electric energy and the future major part of the future smart grid, the renewable energy has received more and more attention from both academia and industry. One of the most important works in the design of renewable energy power generation is converting DC to AC. At present, three-level inverters are widely used in the industry. The advantages of the three-level inverter are: (1) The power quality of the three-level inverter is high. (2) The dV/dt is lower than conventional two-level inverter, which may help solve the problem of unstable situation when many power electronics are working in the power grid.